2021
DOI: 10.1530/erc-20-0469
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and management strategies for pNETs in Von Hippel–Lindau: a systematic review

Abstract: Pancreatic neuro-endocrine tumors (pNETs) in Von Hippel-Lindau (VHL) disease have a relatively good prognosis. However, a subset of pNETs metastasize and significantly contribute to VHL-related mortality. Evidence-based guidelines are needed for timely detection, management and intervention of these tumors. However, the value of several diagnostic tools is controversial and evidence-based management strategies are lacking. This systematic review aims to update current literature on diagnostic and management st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Although germline mutations in these genes have been found in patients with clinically sporadic PNETs, these germline mutations are not always associated with a PNET phenotype. PNETs associated with hereditary tumour syndromes occur most commonly in patients with MEN1 syndrome (~80%), followed by VHL (5–17%) and TSC (4%) ( de Laat et al 2016 , Romanet et al 2019 , Ahmad et al 2021 , Evans et al 2022 b ). Separate from PNETs are poorly differentiated highly aggressive pancreatic neuroendocrine carcinomas (PNECs).…”
Section: Introductionmentioning
confidence: 99%
“…Although germline mutations in these genes have been found in patients with clinically sporadic PNETs, these germline mutations are not always associated with a PNET phenotype. PNETs associated with hereditary tumour syndromes occur most commonly in patients with MEN1 syndrome (~80%), followed by VHL (5–17%) and TSC (4%) ( de Laat et al 2016 , Romanet et al 2019 , Ahmad et al 2021 , Evans et al 2022 b ). Separate from PNETs are poorly differentiated highly aggressive pancreatic neuroendocrine carcinomas (PNECs).…”
Section: Introductionmentioning
confidence: 99%
“…hormone-producing) Pan-NETs present at an early stage due to tumor-related symptoms and complications, non-functional PanNETs (NF-PanNETs) often remain undetected for years. In addition to sporadic tumors, PanNETs frequently occur in inherited endocrine tumor syndromes, such as multiple endocrine neoplasia type 1 (MEN1) and Von Hippel-Lindau disease [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The most characteristic tumours in VHL are hemangioblastoma of the retina and CSN, clear cell renal carcinoma (RCC), pheochromocytoma, and tumour of the inner ear or pancreas. Hemangioblastomas and RCCs are associated with high morbidity and mortality [2,4]. Of all VHL patients, 10-17% develop pNET [1,3].…”
mentioning
confidence: 99%
“…pNET connected with VHL are generally non-functional (rarely cause symptomatic disease) and have metastatic potential, so they should be optimally operated before metastatic spread. Krauss et al reported that significant risk factors of metastatic pNET potential are maximum tumour diameter ≥ 2.8 cm, tumour volume doubling time (≤ 24 months), and the mutation in exon 3especially of codon 161 and 167 [2,4].…”
mentioning
confidence: 99%